Análise fotoelástica da união dente-implante com plataforma switching, sistema de retenção tipo cone morse e roscas quadradas - Adriana Vieira Martins (2013)
The union of teeth and implants initially required as a means to compensate for the lack of stability of the prosthetic implant has become an option restoring the edentulous partial. The aim of this study is to evaluate, by means of photoelasticity, the biomechanics of implant-tooth union, presenting these implants, restorative reduced platform (Platform Switching), restraint Morse Taper and square threads. A pilot study also helped us to provide a basis for choosing the most appropriate photoelastic resin to build models with teeth and / or implants under occlusal loading from four brands of resins widely used in two-dimensional photoelastic test. Four models were constructed: two test models (lower left first premolar and an implant in the region of first molar lower left restored with fixed prostheses three elements in Ni-Cr and lower left second premolar and two implants in region of first and second molars lower left restored with fixed prosthesis five elements in Ni-Cr having a mesial cantilever) and two control models (the same condition above, however, Implant supported). From the master models and choice of resin, four models were obtained in photoelastic resin (Araldite® - Chemicals Ciba S/A of Brazil). They were subjected to two-dimensional photoelastic test. A vertical and concentrated load with magnitude of 150 N was applied at the center of each element of fixed prosthesis. The results indicate lower intensities of tension in the region of the crestal bone implant abutments when attached to natural teeth, or even absence of tension in these regions when compared to the same implant supported condition. Thus, it was concluded that the reduced restorative platform, associated with conical connection and square threads, in the context of union tooth-implant, made the stress distribution in favor of the implant abutments. Furthermore, the four brands of resins evaluated, the Araldite resin was the most suitable for the simulated condition.